The Implementation of Contextual Teaching and Learning Approach on Science Learning in Elementary School - Hery Kresnadi; Ridho Nuryanto; Umi Rawdhatul Islami (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2018)
This study aims to describe the way to apply contextual teaching and learning approach on natural science learning of 6th-grade students of Pontianak Selatan 14 State Elementary School. This research uses qualitative descriptive method. The subjects of this study were researcher, teacher, and all of 6th-grade students of Pontianak Selatan 14 State Elementary School totaling 34 students. Data collection technique which used in this study are two techniques; they are direct observation technique and documents analyze. Instruments which used in this study are direct observation sheet and documents. Based on data analyze obtained, learning planning that uses the contextual teaching and learning approach needs to attention about the continuity between the learning material with the student’s experience in real life and the determination of efficient time allocation. The steps for implementing the contextual teaching and learning approach to natural science learning in Pontianak Selatan 14 State Elementary School have generally been well implemented and have an impact on the mastery of the material even though it has not been maximally individual.